2009
DOI: 10.1159/000260048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gum Chewing on Postoperative Bowel Activity after Cesarean Section

Abstract: Objective: To assess the effects of gum chewing on postoperative bowel function after cesarean section. Material and Methods: Women who underwent cesarean section were randomized to either a gum-chewing group (n = 74) or a non-gum-chewing group (n = 76). The two groups were compared with respect to the return of bowel activity, postoperative analgesic and antiemetic drug requirement and postoperative hospital stay. Results: Bowel sounds appeared in a significantly shorter duration of time in the study group, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
2
38
1
4
Order By: Relevance
“…The studies were generally of moderate quality with minimal publication bias. We evaluated the risk of bias in the 14 published RCTs [13,14,17,21,22,23,24,25,26,27,28,29,30,31](fig. 1) by the Cochrane Risk of Bias Tool [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were generally of moderate quality with minimal publication bias. We evaluated the risk of bias in the 14 published RCTs [13,14,17,21,22,23,24,25,26,27,28,29,30,31](fig. 1) by the Cochrane Risk of Bias Tool [18].…”
Section: Resultsmentioning
confidence: 99%
“…(2) Patients that needed premedication, nasogastric tubes and drains, and those with medical disorders of pregnancy, antepartum hemorrhage, postpartum hemorrhage necessitating blood transfusion, delay in recovery from anesthesia, or need for intensive care postoperatively were excluded [17]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, in previous studies, the time to first bowel sounds in gum-chewing groups ranged from 6.0 to 20.9 hr (Abd-El-Maeboud et al, 2009;Harma et al, 2009;Kafali et al, 2010;Mohsenzadeh Ledari et al, 2013;Satij & Cohen, 2006;Shang et al, 2010), and the time to first flatus ranged from 17.9 to 34.6 hr (Abd- ElMaeboud et al, 2009;Harma et al, 2009;Kafali et al, 2010;Mohsenzadeh Ledari et al, 2013;Satij & Cohen, 2006;Shang et al, 2010). The generally faster recovery of first bowel sounds and flatus in our study may be partly explained by all of our participants having received regional anesthesia, which results in a shorter time to the first passage of flatus than general anesthesia (Kafali et al, 2010;Liu et al, 2009). Another possible explanation for these differences is the use of different types of postsurgical analgesia.…”
Section: Discussionmentioning
confidence: 95%
“…Recent clinical investigations have demonstrated that gum chewing reduces postoperative ileus after gastrointestinal surgery (22,26) and cesarean section (1,23). Since sympathetic hyperactivity is one of the factors that promotes postoperative ileus (33), chewing may contribute to maintaining visceral autonomic balance and gastrointestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%